Pelatihan Pembuatan Flashcard untuk Meningkatkan Budaya Hidup Sehat Siswa Sekolah Dasar Di Wilayah Jakarta - Edwita, Edwita; Hasanah, Uswatun (Universitas Nusantara PGRI Kediri, 2020)
Health is the most essential thing in human life. Healthy behavior is very influential on the growth and development of children in their lives. Children can develop their intellectual power well and must be supported by good nutrition as well, by running a healthy lifestyle. This service activity aims to provide an understanding for teachers to move their students in applying the culture of healthy living. In this case, the dedication team provides a solution in the form of a flashcard as a medium to improve the healthy life culture of elementary school students. The training participants consisted of 107 teachers spread across the Jakarta area. This activity is carried out online using the zoom meeting application. The results of the dedication show that 88% of teachers understand the nature of healthy living culture, how to develop a flashcard based on healthy life literacy and how to motivate students to apply a healthy life culture. These community service activities can contribute and support the government in upholding healthy school programs. A healthy school can foster healthy souls and personalities so as to produce creative and innovative thoughts to advance this nation.